AB0688 GAIT PATTERN DIFFERENCES BETWEEN PATIENTS WITH RADIOGRAPHIC AND NON-RADIOGRAPHIC AXIAL SPONDYLOARTHRITIS, THE MyoSpA STUDY. (2nd June 2020) - Gonçalves, N.; Domingues, L.; Mashayekhi Sardoo, A.; Radu, L.; Rodrigues-Manica, S.; Neto, A.; Torres, R.; Marona, J.; Branco, J.; Mendes, C.; Matias, R.; Pimentel Dos Santos, F.
Abstract : Background: Axial spondyloarthritis (axSpA) is a chronic inflammatory disease classified as radiographic (r-axSpA) or non-radiographic (nr-axSpA). Defining the gait patterns associated with these two groups can improve its detection and promote early intervention. In normal walking, body segments move around the joints as struts of an inverted pendulum. The resultant cyclic rotations contribute to the forward translation of the body, while minimizing muscle work and maintaining stability. Recent literature describes a decline in this pendulum-like mechanism associated with aging and some neurological diseases (Parkinson and multiple sclerosis). Objectives: The aim was to compare the 3D gait kinematics of patients with r-axSpA and nr-axSpA. Methods: A cross-sectional study was conducted on 54 participants (18-50 years old), 27 patients with axSpA (according to ASAS criteria, with less than 10 years since symptoms onset) and 27 healthy controls, matched by gender, age and level of physical activity. A sub-analysis was performed involving the whole group of patients classified as r-axSpA (n=14) and nr-axSpA (n=6). Subjects movement was reconstructed using a 3D full-body kinematic model (Kinetikos, Coimbra, Portugal) fed by 15 inertial sensors placed in the head, arms, trunk, pelvis, thighs, shanks and feet. 3D gait kinematics was characterised based on variables that analyse the body movement as a whole (e.g. center of mass displacement, speed), conventional spatiotemporal parameters (e.g. stance/swing time, step length) and joints kinematics time-normalized to 101 points, comprising the gait cycle from 0 to 100%. Nonparametric statistical tests were used. Results: In the r-axSpA group, 71, 4% were male, with a mean age of 34.43±7.84 years and a BASDAI of 2.84±2.39, whereas in the nr-axSpA, 50% were male, with a mean age of 41.83±6.27 years and a BASDAI of 2.99±0.58. A statistically significant difference was observed in the displacement of the center of mass (with respect to the pelvis local coordinate system) along the anteroposterior axis between the two studied groups (H = 4.96, p = 0.03), with a mean rank displacement of 8.6 for r-axSpA and 15.00 for nr-axSpa, corresponding to a reduction in displacement of 38% (mean 0.00986 vs 0.01579m), in the r-axSpa group. Conclusion: Our preliminary results in r-axSpA subjects show a reduction of the pendulum mechanism. Although no significant segmental (kinematics) changes were observed, the sum of all studied variables result in a clear different gait pattern between the two groups. The observed decline can be an early sign of the inefficiency of the r-axSpA group to minimise the cost of transport of the center of mass during walking (i.e. increased instability). This study shows the potential of gait analysis to identify subjects who may benefit from early physiotherapy intervention. Disclosure of Interests: Nuno Gonçalves: None declared, Lúcia Domingues: None declared, Atlas Mashayekhi Sardoo: None declared, Lucian Radu: None declared, Santiago Rodrigues-Manica Speakers bureau: Jansse, MSD, Novartis, Agna Neto: None declared, Rita Torres: None declared, José Marona: None declared, Jaime Branco Speakers bureau: Vitoria, César Mendes: None declared, Ricardo Matias: None declared, Fernando Pimentel dos Santos Speakers bureau: Novartis, Pfizer, Biogen, Vitoria,